Optimalisasi Fasilitas Area Ruang Tunggu di Bandar Udara Syamsudin Noor Kalimantan Selatan - M. Ikhsan Fauzi; Yuliantoharinugroho, Yuliantoharinugroho (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
This paper aims to determine the Optimization of Injourney Airport Waiting Room Area Facilities in Improving Flight Services at Syamsudin Noor Airport, South Kalimantan. The writing uses a qualitative method with data collection through observation, interviews, documentation and literature studies. The data that has been collected will be analyzed, reduced, then presented to be concluded. The results of the study prove that in general the facilities in the waiting room area of ??Syamsudin Noor Airport, South Kalimantan are quite complete, namely there are gates, toilets, nursery rooms, internet corners, reading corners, workspaces, charger stations, prayer rooms, trolly cabins, dispensers, kids zones, and smoking rooms have been considered quite good and optimal. However, there were factors that hindered the optimization of facilities in the waiting room area, namely the lack of human resources (HR) Facility care and trolly men so that additional human resources (HR) were needed in order to optimize the waiting room area facilities very optimally. Optimization of the waiting room area facilities at Syamsudin Noor Airport continues to be carried out with analysis of passenger needs and routine maintenance. Overall, the existing facilities support passenger comfort and satisfaction while waiting for departure.